IMPLEMENTASI POSISI SEMI FOWLER DALAM MENINGKATKAN SATURASI OKSIGEN PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) : STUDI KASUS - Ridho Akbar Firdaus; T. Eltrikanawati T. Eltrikanawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a pulmonary disorder characterized by shortness of breath, coughing, and excessive sputum production due to damage to the airways (chronic bronchitis) and/or Alveoli (emphysema), which leads to persistent and progressive airflow obstruction. According to data from the World Stroke Organization (2024), COPD causes approximately 3.5 million deaths or about 5% of total global deaths. COPD also ranks seventh as a leading cause of global health problems. If not properly treated, COPD can lead to progressively worsening airflow limitation, resulting in decreased oxygen saturation. One of the interventions that can help improve oxygen saturation is the application of the SemiFowler’s position. The purpose of this case study is to provide emergency nursing care for a COPD patient through the application of the SemiFowler’s position to improve oxygen saturation in the Intensive Care Unit (ICU) of Harapan Bunda Hospital, Batam City. The method used is a case study approach through the stages of the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The results of the case study showed that the application of the SemiFowler’s position for three consecutive days in Mrs. M significantly helped improve oxygen saturation. The increase in SpO₂ was observed from 94% to 96% on the third day. The conclusion of this case study is that the SemiFowler’s position is effective in improving oxygen saturation in patients with COPD.Keywords: COPD, SemiFowler’s Position, Oxygen Saturation